1991
DOI: 10.2527/1991.692664x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a bone biopsy technique for determining the calcium and phosphorus status of swine from weaning to market weight.

Abstract: Tibia biopsies were taken from 75 live pigs at 4-wk intervals and from 251 slaughtered pigs to evaluate bone biopsy as a procedure for determining Ca/P status in pigs fed 70, 85, 100, 115 and 130% of the NRC (1979) estimated dietary Ca and P percentage requirements from weaning to market. Least squares means and SE of live and slaughter biopsy wet weight, ash weight and dry, fat-free ash percentage (DFF%) were compared at each time in each trial and found not to differ. Diet and time effects on ash weight, ash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The width of the bones at the narrow and wide dimensions of the bone shaft was measured. Bones were then refrozen in sealed plastic bags for shear force and shear energy determination as described by Combs et al (1991a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The width of the bones at the narrow and wide dimensions of the bone shaft was measured. Bones were then refrozen in sealed plastic bags for shear force and shear energy determination as described by Combs et al (1991a).…”
Section: Methodsmentioning
confidence: 99%
“…After the shear failure test, wall thickness was measured using dial calipers after the bones were cut in the middle. Shear stress values were calculated according to the formulas of Combs et al (1991a) for metacarpal and of Wilson (1991) for rib. After the shear test, the bones were oven dried at 100°C for 24 h and ashed in a muffle furnace at 600°C for 24 h. Bone ash was expressed as a percentage of the dry weight.…”
Section: Methodsmentioning
confidence: 99%
“…The percent bone ash at necropsy is used to detect osteopenic disease, although methods are not standardized and reference values are not widely published. A bone biopsy technique has been described experimentally 2 ; however, it is unlikely to be developed for field investigation. Recent work in poultry has shown that bone ash-to-bone weight ratios lack sensitivity to detect osteopenic change because bone weight decreases as bone mineralization decreases, leaving the ratio relatively unchanged.…”
mentioning
confidence: 99%
“…Barzel (1969) and Petito and Evans (1984) hydrated chilled and frozen femurs, respectively, of rats for 60 min before weighing them in air and water. Sedlin and Hirsch (1966) (Combs 1989 l.2ll1) when compared with volume and specific gravity that were taken immediately after the bones were taken from the freezer.…”
Section: Mots Cl6s: Densitd Hydratation Os Porcinsmentioning
confidence: 99%